Measurement of gender attitudes to inform gender-transformative approaches: Insights from 4 countries in Sub-Saharan Africa - Ragasa, Catherine; Lambrecht, Isabel B.; Ma, Ning; Cole, Steven (2025)
Motivation - Extensive prior research has demonstrated that reducing gender discrimination enhances women’s empowerment, promotes more inclusive livelihoods, increases agricultural productivity, and improves other development outcomes. - Growing interest on gender-transformative approaches and change indicators, but gaps remain on how to design and measure them - Objective 1: To contribute to the documentation and measurement of gender attitudes that may pose challenges or create opportunities, especially for women working in agrifood systems. - Objective 2: To contribute to the emerging literature on how framing affects the measurement of gender attitudes. - Objective 3: To analyze whether gender-attitude measures align with other commonly used measures of gender (in)equality (e.g., WEAI)